Analysis of Phytochemical Content, Toxicological Assessment, And Evaluation Of Antioxidant Activity In Urtica Dioica L - Drioua, Soufiane; Sikiri, Oumaima; Laabar, Abdelmounaim; Hamri, Ayoub El; Dahak, Hicham; Bouchahta, Hicham; Ameggouz, Mouna; El-Guourrami, Otman; Mojemmi, Brahim; Doukkali, Anass (Journal of Neonatal Surgery, 2025)
This study explores the antioxidant potential of Urtica dioica extracts using different extraction methods, namely infusion and Soxhlet. Antioxidant activity was assessed through DPPH, FRAP, and TAC assays, alongside a phytochemical analysis focused on secondary metabolites such as polyphenols, flavonoids, flavonols, and tannins. Toxicity evaluations were also conducted to ensure safety. The phytochemical investigation employed the Folin–Ciocalteu method for total polyphenols, the AlCl₃ method for flavonoids and flavonols, and the vanillin method for tannins. Acute toxicity studies followed the OECD 423 protocol, using both aqueous and ethanolic extracts. Among all extracts, the ethyl acetate fraction demonstrated the highest polyphenol content (6.613 ± 1.24 mg GAE/g extract), while the aqueous extract recorded the lowest (1.98 ± 0.18 mg GAE/g extract). Similarly, the ethyl acetate extract was richest in flavonoids (45.194 ± 1.04 mg QE/g extract) and flavonols, confirming its superior secondary metabolite content. Conversely, the aqueous extract showed the highest tannin concentration (13.829 ± 0.17 mg CE/g extract). In antioxidant evaluations, the ethyl acetate extract showed the strongest activity in all assays. It registered 78.94 ± 1.84 μg/ml in the DPPH test and 203.27 ± 0.17 μg/ml in the FRAP assay. TAC analysis yielded an IC50 of 18.56 ± 0.001 mg/ml for DPPH, 27.15 ± 0.021 mg/ml for FRAP, and 5.938 mg EAA/g in the TAC test. In contrast, the aqueous extract displayed the weakest antioxidant activity (IC50 = 78.11 ± 0.008 mg/ml for DPPH, 50.37 ± 0.008 mg/ml for FRAP, and 0.128 mg EAA/g in TAC). These findings indicate that the ethyl acetate extract, due to its richness in phenolic compounds, exhibits superior antioxidant properties. Lastly, acute toxicity assessments at 2000 mg/kg showed no clinical signs of toxicity for either aqueous or ethanolic extracts, confirming their safety for further applications.